A QIRA'AH MUBADALAH PERSPECTIVE ON Q.S. AR-RŪM [30]:21 IN UNDERSTANDING THE MARITAL RELATIONSHIP IN THE CASE OF DHI AND LYANA - Vania Hanifa; Mohamad Mualim; Khoirun Nidhom (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study examines the marital relationship between Dhi and Lyana through the lens of Qirā'ah Mubādalah in interpreting Q.S. Ar-Rūm [30]:21. This study is motivated by the limited integration of Qirā'ah Mubādalah into interpretations of Q.S. Ar-Rūm [30]:21, as previous studies have generally interpreted the verse from a normative perspective or applied Qira'ah Mubadalah primarily to discussions of nushūz in Q.S. An-Nisā' [4]:34 and [4]:128. This study employs a qualitative case study design based on one year of participant observation complemented by library research. The findings demonstrate that sakinah, mawaddah, and raḥmah constitute shared rights and shared responsibilities of both spouses grounded in the principle of reciprocity. The case of Dhi and Lyana further shows that unilateral polygamy, arranged marriage without a strong emotional bond, and nushūz understood as a relational problem undermine the foundation of an egalitarian marital relationship. This study demonstrates that Qira'ah Mubadalah provides a more contextual interpretation of Q.S. Ar-Rūm [30]:21 by positioning it as a theological foundation for understanding and fostering marital relationships that are just, reciprocal, and oriented toward maṣlaḥah within contemporary Muslim families.